Structural and In Vivo Studies on Trehalose-6-Phosphate Synthase from Pathogenic Fungi Provide Insights into Its Catalytic Mechanism, Biological Necessity, and Potential for Novel Antifungal Drug Design - Miao, Yi (mBio, 2017)
The disaccharide trehalose is critical to the survival of pathogenic fungi in their human host. Trehalose-6-phosphate synthase (Tps1) catalyzes the first step of trehalose biosynthesis in fungi. Here, we report the first structures of eukaryotic Tps1s in complex with substrates or substrate analogues. The overall structures of Tps1 from Candida albicans and Aspergillus fumigatus are essentially identical and reveal N- and C-terminal Rossmann fold domains that form the glucose-6-phosphate and UDP-glucose substrate binding sites, respectively. These Tps1 structures with substrates or substrate analogues reveal key residues involved in recognition and catalysis. Disruption of these key residues severely impaired Tps1 enzymatic activity. Subsequent cellular analyses also highlight the enzymatic function of Tps1 in thermotolerance, yeast-hypha transition, and biofilm development. These results suggest that Tps1 enzymatic functionality is essential for the fungal stress response and virulence. Furthermore, structures of Tps1 in complex with the nonhydrolyzable inhibitor, validoxylamine A, visualize the transition state and support an internal return-like catalytic mechanism that is generalizable to other GT-B-fold retaining glycosyltransferases. Collectively, our results depict key Tps1-substrate interactions, unveil the enzymatic mechanism of these fungal proteins, and pave the way for high-throughput inhibitor screening buttressed and guided by the current structures and those of high-affinity ligand-Tps1 complexes.